2004
DOI: 10.1065/espr2004.08.213
|View full text |Cite
|
Sign up to set email alerts
|

Utilising the Synergy between Plants and Rhizosphere Microorganisms to Enhance Breakdown of Organic Pollutants in the Environment (15 pp)

Abstract: A better knowledge of plant-microbial interactions will provide a basis for improving the efficacy of biological remediations. Further research is, however, needed to investigate different feedback mechanisms that select and regulate microbial activity in the rhizosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
245
1
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(273 citation statements)
references
References 144 publications
5
245
1
7
Order By: Relevance
“…Most of these chemicals are of great environmental concern due to the known or potential genotoxicity and carcinogenicity, such as benzo[a]-pyrene. Numerous studies have focused on the fate and transport of these chemicals (Moon et al 2003, Palm et al 2004 and application of remedial technologies to manage those (Iturbe et al 2004, Chaudhry et al 2005, Trably & Patureau 2006. Due to the different intrinsic physicochemical properties of individual PAHs, such as solubility, vapor pressure and lipophilicity, they tend to interact to different extents with sediments, SPM, and biota (Broman et al 1996 1997, Zhou & Maskaoui 2003), and are subject to various transformation processes including chemical transformation, biodegradation and photochemical degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these chemicals are of great environmental concern due to the known or potential genotoxicity and carcinogenicity, such as benzo[a]-pyrene. Numerous studies have focused on the fate and transport of these chemicals (Moon et al 2003, Palm et al 2004 and application of remedial technologies to manage those (Iturbe et al 2004, Chaudhry et al 2005, Trably & Patureau 2006. Due to the different intrinsic physicochemical properties of individual PAHs, such as solubility, vapor pressure and lipophilicity, they tend to interact to different extents with sediments, SPM, and biota (Broman et al 1996 1997, Zhou & Maskaoui 2003), and are subject to various transformation processes including chemical transformation, biodegradation and photochemical degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of vegetation is known to enhance microbial populations within soil (see reviews by Hutchinson, 2003, Wenzel, 2008and Khan et al, 2013 and accordingly to improve degradation of soil contaminants due to co-metabolic processes (Chaudhry et al, 2005;Gaskin et al, 2008). For example, higher counts of culturable microbes and actinomycetes were found in vegetated soil when compared to un-vegetated soil, coupled with a 15.6% decrease in final TPH concentrations (Liste and Felgentreu, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As in other studies, contaminant degradation was found to be higher in plants that showed slight signs of stress and growth depression (Philips et al, 2009;Liste and Felgentreu, 2006). It appears that, for at least some species, moderately stressful conditions augment effective phytoremediation due to stress stimulated chemical release, which increases microbial populations and promotes the level of hydrocarbon degradation (Kamath et al, 2004;Chaudhry et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The negative environmental impacts and high costs associated with excavating and transporting contaminated soils for off-site processing and treatment have led the Australian Antarctic Division (AAD) to abandon dig-and-haul methods in favour of implementing alternative onsite in situ remediation techniques [2,3]. The in situ techniques utilised on subantarctic Macquarie Island include injection of nutrients and aeration into the soils, both of which promote natural attenuation by encouraging hydrocarbon-degrading microbes [3,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%